PESTICIDE USE AGAINST PESTS - Артиков Орифжон Обидович (Web of Journals Publishing, 2025)
The article presents the current significance of chemical preparations used against pests of agricultural crops and the classification of pesticides.
Keywords: Productivity, plant, pest, insect, chemicals.